Thermal conductivity of aerogel composites with oriented nitrogen-doped graphene. (7th July 2017) - Yue, Chenwu; Feng, Jian; Feng, Junzong; Jiang, Yonggang
Abstract: Aerogels with oriented sheets show better thermal insulation properties. However, it is difficult to prepare bulk oriented aerogels. In this paper, we prepared this kind of aerogels by using aligned fibers as the wall of galleries. This simple method makes the N-doped graphene sheets align along the in-plane orientation during impregnating. The as-prepared aerogel composites not only show much lower through-plane thermal conductivity (26.6–29.8 mW m −1 K −1 ) compared to their in-plane thermal conductivity (44.9–55.1 mW m −1 K −1 ), but also exhibit high tensile strength (higher than 3 MPa). After being heat treated at 300 °C, the through-plane thermal conductivity (23.3 mW m −1 K −1 ) is even lower than the thermal conductivity of pure aerogels. These properties significantly contribute to their applications in thermal insulation. Besides, the simple method is also useful in preparing other materials with oriented sheets and high strength.